Memahami Penerapan Model Kurikulum Darurat di Masa Pandemi Covid-19: Kasus Pembelajaran Matematika SD/MI di Indonesia - Shobiroh Nia Ulfa Kurniyawati; Andi Andi Prastowo (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2021)
This study aims to find a solution to the problems of implementing the emergency curriculum model in SD/MI, especially in mathematics during the covid 19 pandemic. This research was motivated by the various obstacles experienced by educators and students in the teaching and learning process that applied the emergency curriculum model. in school at the elementary level. The approach used in this research is descriptive qualitative method, with interview techniques to classroom teachers in SD/MI. Researchers conducted interviews with four teachers who teach at different schools and come from various regions both from Java and outside Java, namely at MIN 1 Murung Raya, Central Kalimantan, MIN 1 North Lampung, SD NU Sleman, and teachers at MI Private Darul Huda Ngaglik Sleman. Given the conditions that made it impossible for researchers to meet with resource persons from various regions, researchers collected data by telephone or sending private messages via Whatsapp and voice notes so that all the data needed in this research process was obtained. The results of this study are found various obstacles as well as alternative solutions that will be given in overcoming the implementation of the emergency curriculum in the hope that it can be used as a reference for readers when facing the same obstacles as written in this article.